A Survey: Different Approaches to Integrate Data Using Ontology and Methodologies to Improve the Quality of Data: - Sowmya Devi, L; Jai Barathi, B; MS, Hema (International Journal of Computer Sciences and Engineering, 2014)
This In today’s world, the amount of data is increasing tremendously. In order to analyze data and make decisions, data residing at different sources are integrated. Data integration is an approach to integrate data from different data sources. Data federation is a data integration strategy used to create integrated virtual view. This paper deals with various approaches of data integration to resolve semantic heterogeneity using ontology. Various ontology based data integration techniques are reviewed and issues are summarized. Different metrics and approaches are also discussed to improve the quality of the data.